The ict's: a tool for learning to enhance recreation (Revista Electrónica REDINE, 2018)
This essay presents some thoughts on the use of Information Technology and Communication as a recreational tool, used to promote learning in education, for it was conducted a literature review and an analysis of the theoretical foundations independently support these practices. Of course, the legal and curricular support those skills were revised in order to leave raised a number of recommendations to enable the teacher to guide the use of ICTs through recreation and thus contribute next to "Project Canaima "a quality education, where technology is the starting point for integrating program content and produce meaningful learning.
Keywords: ICT; recreation; learning